STUDY ON FOLKLORE MEDICINAL PRACTICES OF PANIYA TRIBES FOR GYNAECOLOGICAL AILMENTS. - ABDULLA NASEEF S.A; AJESH T.P; KUMUTHAKALAVALLI .R (International Journal of Pharma and Bio Sciences, 2012)
The present world is keen in providing good medical services in every field related. Among them gynaecology is getting deep focus in every sense from the pregnancy to the end of the child hood of the baby as well as mother. The world faces big problem by the use of chemical based medicines. Seeking alternative through traditional medicine would be the only viable solution. However the execution of this system can only be possible through documenting and standardising the folklore medical practices from the tribes who are the repository of traditional knowledge. Paniya tribe is the very prominent folklore group of Kerala especially in Wayanad. In the present study 32 plant species from 30 genera belongs to 25 families have been recorded as medicinal plants against gynaecological problems and members from Fabaceae are the predominant among them.